2019
DOI: 10.9734/jerr/2019/v5i316926
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining and Statistical Analysis for Available Budget Allocation Pre-procurement of Manufacturing Equipment

Abstract: In a situation where a decision maker faces problems of allotting the available budget on the strategic decisions in a manufacturing industry, data information plays an important role to maintain long run profit in the industry. Statistical analysis was incorporated to determine the correlational strength between the number of years and each of the strategic decisions, their confidence level, and the predicted values. This study identified the strategic areas of addressing the issues which are machine (), acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Ojo et al [16] Used Statistical Analysis Software (SAS) to determine the correlational strength between the number of years of procurement and each of the strategic decisions, their confidence interval and predicted the costs for subsequent procurement. This study is a continuation of a published work where multiobjectives optimization was considered over the strategic decisions.…”
Section: Resultsmentioning
confidence: 99%
“…Ojo et al [16] Used Statistical Analysis Software (SAS) to determine the correlational strength between the number of years of procurement and each of the strategic decisions, their confidence interval and predicted the costs for subsequent procurement. This study is a continuation of a published work where multiobjectives optimization was considered over the strategic decisions.…”
Section: Resultsmentioning
confidence: 99%
“…It is a way to get information from data and also a tool for creating an understanding from a set of numbers [9,10]. Ojo et al, [11], used statistical analysis to determine the correlational strength between the years of procurement of the machines, accessories, spareparts and miscellaneous and the amount spent on the selected decisions, they also find their confidence level, and predicted the values for subsequent procurement using Statistical Analysis Software (SAS). Yongwei et al, [12], identified the effectiveness of a particular set of important management programs in improving construction labor productivity.…”
Section: Fig 1 Labor Productivity Through Methods Studymentioning
confidence: 99%